2020
DOI: 10.1016/j.ebiom.2019.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of novel ADPKD drug candidates from disease-stage specific gene expression profiles

Abstract: Background: Autosomal Dominant Polycystic Kidney Disease (ADPKD) is one of the most common causes of end-stage renal failure, caused by mutations in PKD1 or PKD2 genes. Tolvaptan, the only drug approved for ADPKD treatment, results in serious side-effects, warranting the need for novel drugs. Methods: In this study, we applied RNA-sequencing of Pkd1cko mice at different disease stages, and with/ without drug treatment to identify genes involved in ADPKD progression that were further used to identify novel drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 67 publications
4
14
0
Order By: Relevance
“…In line with the aforementioned raised concerns, our findings revealed that the selection of appropriate housekeeping genes and consequent use of Ppia as the reference, allowed the detection of differences between groups regarding Stat3 expression, thought to be upregulated in kidney cysts and associated with PKD progression in mouse models 8 , 54 60 . On the other hand, the normalization using Gapdh showed no difference.…”
Section: Discussionsupporting
confidence: 69%
“…In line with the aforementioned raised concerns, our findings revealed that the selection of appropriate housekeeping genes and consequent use of Ppia as the reference, allowed the detection of differences between groups regarding Stat3 expression, thought to be upregulated in kidney cysts and associated with PKD progression in mouse models 8 , 54 60 . On the other hand, the normalization using Gapdh showed no difference.…”
Section: Discussionsupporting
confidence: 69%
“…The stage is now set for a Phase 2 parallel-arm multicentre trial of pioglitazone in ADPKD. With no options to slow disease progression in the last 150 years, new treatment possibilities for ADPKD are now rapidly emerging, including drug-repurposing approaches [ 20 , 21 ]: PPAR-γ agonists could yet find a new lease on life in the treatment of ADPKD.…”
Section: Introductionmentioning
confidence: 99%
“…Pioglitazone; a well-known anti-diabetic drug that is a peroxisome proliferator-activated receptor gamma (PPAR-γ) agonist, has been found to suppress the development of renal cyst in the preclinical studies via different mechanisms which inarguably suggests its pleiotropy. The characteristic property to improve the molecular and phenotypic defects with a lower risk of adverse effects in preclinical animal models has proved pioglitazone an excellent and emerging candidate to treat ADPKD (Liu et al 2020 ; Raphael et al 2009a ; Malas et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%